“Transfer Prices and Profit Maximization in Multinational Enterprise Operations”: Comment - Pugel, Thomas A.; Ugelow, Judith L. (Journal of International Business Studies, 1982)
A recent article by D. J. Fowler in this journal considers the use of transfer pricing by multinational enterprises (MNEs) as a mechanism for increasing global after-tax profits.1 Fowler focuses on the operation of a Canadian subsidiary by a U.S. MNE. This comment observes several mathematical errors in Fowler's study; in addition the authors argue that the variation in tariff rates deserves more emphasis than it receives in Fowler's study, and that the variation in levels of foreign ownership deserves less emphasis. Based upon these changes, Fowler's key table is recomputed and the empirical results for all but one industry are shown to be consistent with theoretical predictions.